Production of acetone-butanol-ethanol from sago pith residues - Linggang, Siren (2012)
Sago pith residues are one of the abundant lignocellulosic residues that left behind after starch extraction process and contains significant amount of starch (58%), cellulose (23%), hemicellulose (9.2%) and lignin (3.9%). This residue has a great potential as cheap and affordable substrate for the production of enzymes,fermentable sugars and biofuel due to their high content of cellulose and hemicellulose. This study was carried out to produce fermentable sugars from sago pith residues using crude cellulases produced from local fungal isolates namely Trichoderma asperellum UPM1 and Aspergillus fumigatus UPM2 either individual or in combination. The fermentable sugars produced were then converted to acetonebutanol-ethanol (ABE) by Clostridium acetobutylicum ATCC 824. In this study,crude cellulases produced from Aspergillus fumigatus UPM2 exhibited high specific cellulases activity (0.77 U/mg FPase, 47.76 U/mg CMCase and 1.56 U/mg β-glucosidase) as compare to crude cellulases from Trichoderma asperellum UPM1 and mixed cultures. Therefore, crude cellulases produced from Aspergillus fumigatus UPM2 was used for further study. Enzymatic hydrolysis using crude cellulases produced by Aspergillus fumigatus UPM2 based on 23.4 I.U of β-glucosidase as ratelimiting released approximately 21 g/L fermentable sugars from 5% (w/v) sago pith residues at pH 5.0 and temperature of 50ºC. The hydrolysis yield obtained was 73% which were comparable with the hydrolysis yield of maize straw (66%) and rice straw (70%) as reported in earlier studies by other researchers. High Performance Liquid Chromatography (HPLC) analysis on sago pith residues hydrolysate showed that it consisted mainly of glucose (10 g/L) and cellobiose (4.26 g/L). The total acetone-butanol-ethanol (ABE) production by Clostridium acetobutylicum ATCC 824 using concentrated sago pith residues hydrolysate with addition 0.5 g/L yeast extract was 8.84±0.20 g/L (5.41±0.10 g/L of butanol) after 72 hours of fermentation. Yield and productivity of the total acetone-butanol-ethanol were 0.30 g ABE/g glucose and 0.12 g/L/h, respectively. This result was almost comparable to the result obtained using synthetic glucose (40 g/L) for ABE production by Clostridium acetobutylicum ATCC 824 which the yield and productivity were 0.32 g ABE/g glucose and 0.15 g/L/h, respectively.